INTRODUKSI TEKNOLOGI “MOTO KOH PADEE”: Studi Antropologi Pertanian di Aceh Utara - Putri Ananda Saka (Department of Anthropology, 2018)
This study examines the introduction of Mooto Kooh Padeee technology to the community of Meurah Mulia, Aceh. The data obtained are qualitative data using data collection techniques in the form of observation, in-depth interviews, data analysis, documentation studies, literature studies, and literature studies. While the theory used as supporting analysis is Clifford Geertz's thinking about agricultural involution. The process of introducing and educating agricultural technology has begun to be intensively carried out in farming communities in rural Aceh. Including the District of Meurah Mulia, North Aceh District which experienced the introduction of Koh Padee moto harvesting technology. In the process of entering the innovation, of course experiencing various responses from the public. This is what is studied more deeply about how acceptance and rejection take place. Furthermore, the new value brought by the new technology has changed the pattern and culture of agriculture and the structure of its society. This is also analyzed in this study.